Reúso do gesso na construção civil em substituição à cal para pintura : mitigando impactos ambientais - Santos, Ítalo José Silva (2022)
Civil construction is one of the most important segments for the economic and social development of a country. The issue is the environmental impacts caused by this activity, including the waste production from construction sites, such as gypsum residue. Among the ways to contribute to reduce the impacts are practices like reduction, reuse and recycling civil construction waste. Gypsum is increasingly present in works, being widely used in internal building linings and, due to this, creates a high volume of residues, corresponding to approximately 4% to 15% of total waste generated at a construction site. Once improperly disposed, these residues occupy large areas, cause surface and groundwater leaching, in addition to creating dust and demanding high costs for maintenance and monitoring. In 2011, the National Environment Council – CONAMA – amended article 3rd of Resolution number 307/2002, defining a new rating for gypsum waste, for which there was previously no viable technology or application for recycling or recovery and, since then, must be reused or recycled. Therefore, the present research aimed to propose an alternative to mitigate environmental impacts from reusing gypsum waste generated in construction works in Aracaju-SE. The methodology was based on the hypothetical-deductive method, opting for a descriptive, exploratory, quantitative and qualitative research. The hypothesis considered was that such residues can be reused in paintings to replace whitewash. Data were collected through bibliographic and documentary sources; forms applied to construction workers, recycling cooperatives, waste management companies and public institutions that perform urban services; and by carrying out experiments. Data analysis was divided into three topics: first on the assessment of interest of potential users to reuse gypsum waste in their professional activities; second analyzed the potential for reuse of gypsum residues in paintings, replacing whitewash; and third addressed the acceptance of potential consumers after testing gypsum waste in application of paints. Analysis revealed that is feasible to reuse gypsum waste from construction in the application of paints to replace whitewash. Thus, this becomes a proposal to reduce the environmental impacts caused by inadequate destination of gypsum waste.